Acute Abdomen in Pregnancy due to Idiopathic Chylous Ascites - Claudia Epelde; Fátima Saravia; Mónica Aguinaga; Ane Toledo; Arantza Lekuona; Mikel Gorostidi (Hindawi Limited, 2024)
Chylous ascites results from the leakage of lymph rich in lipids into the peritoneal cavity and represents an exceedingly rare event in the course of pregnancy. While there are numerous documented instances of this pathology manifesting with hypogastric or diffuse abdominal pain, our report highlights a unique presentation involving a 35-week pregnant woman experiencing severe epigastric pain unrelated to pregnancy-induced hypertension or other gastrointestinal disorders. Major acute obstetric pathologies were ruled out, and there was no evidence of fetal distress. Due to uncontrolled pain with an unidentified etiology and an unfavorable Bishop score, an urgent cesarean section was performed. A copious amount of milky fluid was observed during the surgery, subsequently confirmed as chylous in nature. Both the newborn and the mother had positive outcomes postsurgery. Although it is usually a benign condition, it is important for healthcare professionals to be aware of this entity in order to provide timely medical care and administer appropriate treatment.